Nepal : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
Nepal has a well-established process for preparing periodic development plans, having prepared nine such plans earlier. Typically, the preparation of the new plan starts with the mid-term review of the ongoing plan, which serves as a base for the Approach Paper for the new plan. The Approach Paper, which provides broad guidelines and targets an indicative resource framework for the new plan, is approved by the National Development Council (NDC). The plan is then prepared and finalized after discussion and approval by the National Planning Commission and then by the Cabinet.